Does one workshop on respecting cultural differences increase health professionals' confidence to improve the care of Australian Aboriginal patients with cancer? An evaluation - Durey, Angela; Halkett, Georgia; Berg, Melissa; Lester, L.; Kickett, Marion (BioMed Central, 2017)
© 2017 The Author(s). Background: Aboriginal Australians have worse cancer survival rates than other Australians. Reasons include fear of a cancer diagnosis, reluctance to attend mainstream health services and discrimination from health professionals. Offering health professionals education in care focusing on Aboriginal patients' needs is important. The aim of this paper was to evaluate whether participating in a workshop improved the confidence of radiation oncology health professionals in their knowledge, communication and ability to offer culturally safe healthcare to Aboriginal Australians with cancer. Methods: Mixed methods using pre and post workshop online surveys, and one delivered 2 months later, were evaluated. Statistical analysis determined the relative proportion of participants who changed from not at all/a little confident at baseline to fairly/extremely confident immediately and 2 months after the workshop. Factor analysis identified underlying dimensions in the items and nonparametric tests recorded changes in mean dimension scores over and between times. Qualitative data was analysed for emerging themes. Results: Fifty-nine participants attended the workshops, 39 (66% response rate) completed pre-workshop surveys, 32 (82% of study participants) completed post-workshop surveys and 25 (64% of study participants) completed surveys 2 months later. A significant increase in the proportion of attendees who reported fair/extreme confidence within 2 days of the workshop was found in nine of 14 items, which was sustained for all but one item 2 months later. Two additional items had a significant increase in the proportion of fair/extremely confident attendees 2 months post workshop compared to baseline. An exploratory factor analysis identified three dimensions: communication; relationships; and awareness. All dimensions' mean scores significantly improved within 2 days (p < 0.005) and persisted to 2 months. The workshop raised awareness about barriers and enablers to delivering services respectful of cultural differences, led to a willingness to reflect on pre-existing beliefs and assumptions about Aboriginal Australians that in some cases resulted in improved care. Conclusion: Single workshops co-delivered by an Aboriginal and non-Aboriginal presenter can be effective in building health professionals' confidence and translating into practice knowledge of respectful care of Aboriginal patients with cancer. Sustaining improvements may require integrating this approach into ongoing professional development.